2018
DOI: 10.1007/s00787-018-1205-1
|View full text |Cite
|
Sign up to set email alerts
|

Social skills group training in children with autism spectrum disorder: a randomized controlled trial

Abstract: In 122 high-functioning children with autism spectrum disorder (ASD; 9–13 years; 19 girls), we investigated the effectiveness of a 15-session social skills group training (SST) with and without parent and teacher involvement (PTI) in a randomized controlled trial with three conditions: SST ( n = 47), SST–PTI ( n = 51), and care-as-usual (CAU, n = 24). Hierarchical linear modeling was used for immediate and 6-month follow-up analyses. Measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 19 publications
4
30
0
2
Order By: Relevance
“…That is, more children in this subgroup participated in SST without parent and teacher involvement than in SST with such involvement. In the comparison between the three conditions of the RCT that the current paper was based on, we found no difference across all participants between the effect of SSTs with or without parent and teacher involvement compared to CAU reported by parents (Dekker et al 2019). Yet, taking into account individual differences, the current study indicates that no formal parent and teacher involvement negatively affects outcome on SST for those children with poor social communicative skills and high perceived difficulty of these skills as reported by parents at start.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…That is, more children in this subgroup participated in SST without parent and teacher involvement than in SST with such involvement. In the comparison between the three conditions of the RCT that the current paper was based on, we found no difference across all participants between the effect of SSTs with or without parent and teacher involvement compared to CAU reported by parents (Dekker et al 2019). Yet, taking into account individual differences, the current study indicates that no formal parent and teacher involvement negatively affects outcome on SST for those children with poor social communicative skills and high perceived difficulty of these skills as reported by parents at start.…”
Section: Discussionmentioning
confidence: 57%
“…The study was based on data from an RCT on the effectiveness of group SST with and without parental and teacher involvement, with three conditions: Social Skills Training (SST; n = 47), Social Skills Training with Parent and Teacher Involvement (SST-PTI; n = 51) and CAU (n = 24) (Dekker et al 2014(Dekker et al , 2019. From September 2010 through September 2013, training groups had started (September and February), data collection therefore started in May 2010 (first pre test) and ended in October 2014 (last follow-up measurement).…”
Section: Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the included studies fell within the Some Risk-of-Bias category and evidence of bias was also evident at the study-level through funnel plot analysis (Borenstein et al 2009). Notably, the three largest studies (Choque Olsson et al 2017;Dekker et al 2019;Freitag et al 2016) had relatively smaller effects, though they demonstrated the highest precision, resulting in an asymmetric funnel plot. This suggests that the magnitude of the overall effect may be positively biased and that further studies with similarly large samples should be conducted in order to gain more accurate and precise estimates of the overall effects.…”
Section: Limitationsmentioning
confidence: 99%